2010
DOI: 10.1074/jbc.m110.134536
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Induce Hyaluronan Synthesis and Monocyte Adhesion in Human Endothelial Cells through Hyaluronan Synthase 2 (HAS2) and the Nuclear Factor-κB (NF-κB) Pathway

Abstract: Chronic inflammation is now accepted to have a critical role in the onset of several diseases as well as in vascular pathology, where macrophage transformation into foam cells contributes in atherosclerotic plaque formation. Endothelial cells (EC) have a critical function in recruitment of immune cells, and proinflammatory cytokines drive the specific expression of several adhesion proteins. During inflammatory responses several cells produce hyaluronan matrices that promote monocyte/macrophage adhesion throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
97
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 40 publications
10
97
2
2
Order By: Relevance
“…Especially, HA is produced by both ECs and VSMCs, and its deposition creates a hygroscopic environment suitable for cell migration (16,17). In accordance with a previous study in human umbilical vein endothelial cells (HUVECs) (18), only HAS2 and HAS3 mRNA were detected in HPAECs. We showed that BMP9 and BMP10 specifically regulated HAS2 mRNA expression.…”
Section: Discussionsupporting
confidence: 65%
“…Especially, HA is produced by both ECs and VSMCs, and its deposition creates a hygroscopic environment suitable for cell migration (16,17). In accordance with a previous study in human umbilical vein endothelial cells (HUVECs) (18), only HAS2 and HAS3 mRNA were detected in HPAECs. We showed that BMP9 and BMP10 specifically regulated HAS2 mRNA expression.…”
Section: Discussionsupporting
confidence: 65%
“…Increased concentrations of HA indicate that its metabolism is altered in cancer cells, and the imbalance of HA synthesis and/or degradation may play an important role in tumor progression (33). HAS2 mainly produces high molecular weight HA (200-2000 kDa) and it is involved in a variety of both pathological and physiological activities, including proliferation, differentiation, inflammation, epithelial to mesenchymal transition (EMT) and cancer progression (38)(39)(40). Furthermore, it was recently reported that HAS2 plays an important prometastatic role by generating a favorable microenvironment of cancer stem-like cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] In vitro studies have shown that inflammatory cytokines, particularly IL-1, IL-6, and TNF-a, as well as reactive oxygen species are involved in the degradation of HA. [32][33][34] High serum levels of HA have been reported in CKD [35][36][37] and seem to be a risk predictor of poor survival in dialysis. 38 However, the mechanisms underlying the increased levels have not been fully explained.…”
Section: Discussionmentioning
confidence: 99%